Effectiveness of Multimedia Instruction Based on Cognitive Theory on Academic Motivation and Mathematics Achievement for Students in Distance Education Centers - Amir Pourahmadali; Morteza Farahani; Aliakbar Sheikhi Fini (Iranian Journal of Educational Research, 2025)
Objective: The primary objective of the current investigation is to explore the effect of multimedia instruction based on cognitive theory on academic motivation and mathematics achievement for students in distance education centers. Methods: The methodological approach employed in this inquiry is quasi-experimental, utilizing a pre-test-post-test design in conjunction with a control group. The statistical population encompasses all first-year secondary school students enrolled in distance education centers situated in the 2nd Education District of Arak city. A cluster random sampling technique was implemented, whereby two distance education centers were randomly selected from the specified population, and 40 participants from these centers were randomly allocated into experimental and control groups following a matching process. The control group was subjected to traditional educational practices prevalent in distance education centers, whereas the experimental group was instructed in the first and second chapters of mathematics for first-year secondary students through the utilization of multimedia developed by the researcher. Data were acquired via a researcher-developed mathematics academic achievement scale and the educational motivation scale, both of which demonstrated confirmed validity and reliability. Results: The outcomes derived from the multivariate analysis of covariance indicate a statistically significant advantage of the experimental group concerning the variables of mathematics achievement and academic motivation among students. Conclusions: The results of our investigation substantiate the significance of multimedia instruction in enhancing academic performance and educational motivation, thereby indicating its efficacy as a pedagogical strategy for educators.